2014
DOI: 10.1051/0004-6361/201424027
|View full text |Cite
|
Sign up to set email alerts
|

Period and amplitude variations in post-common-envelope eclipsing binaries observed with SuperWASP

Abstract: Period or amplitude variations in eclipsing binaries may reveal the presence of additional massive bodies in the system, such as circumbinary planets. Here, we have studied twelve previously-known eclipsing post-common-envelope binaries for evidence of such light curve variations, on the basis of multi-year observations in the SuperWASP archive. The results for HW Vir provided strong evidence for period changes consistent with those measured by previous studies, and help support a two-planet model for the syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 56 publications
4
36
0
Order By: Relevance
“…13 927 light curves were downloaded from the SuperWASP archive, and a form of the custom IDL code described in Lohr et al (2014), modified for large numbers, was run on them. This checked and refined the orbital period associated with each object identifier, searching within a range centered on the catalogue period (itself derived from the archive database); produced a phase-folded light curve and mean fitting curve (with 100 bins); generated O−C, amplitude change and absolute flux change diagrams; and determined a rate of period change where this was supported by the O−C diagram.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 927 light curves were downloaded from the SuperWASP archive, and a form of the custom IDL code described in Lohr et al (2014), modified for large numbers, was run on them. This checked and refined the orbital period associated with each object identifier, searching within a range centered on the catalogue period (itself derived from the archive database); produced a phase-folded light curve and mean fitting curve (with 100 bins); generated O−C, amplitude change and absolute flux change diagrams; and determined a rate of period change where this was supported by the O−C diagram.…”
Section: Methodsmentioning
confidence: 99%
“…All output files were checked down to a ratio of 1.25, below which it was generally difficult to judge the classification reliably by eye; tests applied to eclipsing post-common-envelope binaries in Lohr et al (2014) had also indicated that ratios below 1.05 did not generally indicate statistically significant period change. This meant that 679 EWtype, 436 EB-type and 806 EA-type objects were checked visually, and assigned a classification: plausible quadratic variation in the O−C diagram (supporting secular period change); plausible sinusoidal variation (supporting alternating period increases and decreases); no apparent period change (usually due to erratic time sampling misleading the program's fitting algorithm); erroneous period found (usually due to the original input period being significantly wrong); or unclear (usually when the time sampling was very sparse or the time basis very limited).…”
Section: Methodsmentioning
confidence: 99%
“…SuperWASP data has been included where this fills significant gaps in the historic data; when included we used the same binning methodology as Lohr et al (2014). Error bars are shown where timing uncertainties have been included in published data and did not affect the readability of the diagram.…”
Section: Analysis Of Eclipse Timingsmentioning
confidence: 99%
“…(The fainter duplicate object J093012 has 5950 points covering the same time span; its data were used here as a check on the results found for J093010.) For reference, SuperWASP exposure lengths are 30 s. Initial values for the orbital periods of the two eclipsing binaries were found with a custom IDL code described in Lohr et al (2014b): 19 674.594 ± 0.005 s and 112 799.10 ± 0.15 s; then a second code was written to separate the two eclipsing signals. The light curve was first folded on the shorter period corresponding to the contact binary, and phase-binned to give a smooth mean curve (90 bins were used); an optimally-weighted average was then found for the data points in each bin (which corresponded closely to the visible contact binary signal).…”
Section: Photometrymentioning
confidence: 99%